The prognostic value of red cell distribution width to serum calcium ratio in 28-day all-cause mortality among intensive care unit patients with acute kidney injury： a retrospective analysis based on data mining in the MIMIC-IV database - Meng Yuan; Ouyang Yi; Zhou Yu; Tan Ren-xiang; Xiao Bi-xia; Yuan Ze-dong-fang; Chen Ren-shan (Linchuang shenzangbing zazhi, 2025)
ObjectiveTo explore the relationship between red blood cell distribution width to serum calcium ratio （RCR） and 28-day all-cause mortality in patients with acute kidney injury （AKI） admitted to the intensive care unit （ICU）， and to evaluate the predictive value of RCR for the prognosis of AKI in ICU patients.MethodsClinical data of 8，814 adult patients with AKI enrolled in the Medical Information Mart for Intensive Care Ⅳ （MIMIC-Ⅳ） in the United States between 2008 and 2019 were retrospectively analyzed. The 28-day all-cause mortality was set as the outcome measure. The cut-off value was determined using restricted cubic splines （RCS）， and patients were classified into high-RCR and low-RCR groups. Kaplan-Meier survival analysis， Cox proportional-hazards regression model， and RCS were employed to analyze the relationship between RCR and the 28-day all-cause mortality of AKI in ICU patients. The receiver operating characteristic （ROC） curve was utilized to evaluate the predictive efficacy of RCR for the 28-day all-cause mortality of AKI in ICU patients. Finally， subgroup stratification analysis was conducted with relevant covariates to verify the robustness of the results.ResultsAmong 8，814 participants， males accounted for 58.5%， with an average age of （68.4±16.2） years. The 28-day all-cause mortality was 24.3%. The cut-off value determined by RCS was 1.926. The Cox proportional-hazards regression model showed that after adjusting for confounding factors， RCR was significantly correlated with the 28-day all-cause mortality of AKI in ICU patients （HR=1.369，95%CI：1.312-1.707，P<0.001）. The 28-day all-cause mortality in the high-RCR group increased by 19.2% than the low-RCR group （HR=1.192，95%CI：1.024-1.373，P<0.001）. RCS analysis indicated a non-linear increase in the association between RCR and the 28-day all-cause mortality of AKI in ICU patients （χ2=24.67， P<0.001）. The Kaplan-Meier survival curve showed that the cumulative 28-day survival rate of ICU patients with AKI in the high-RCR group was lower. The ROC curve showed that the area under the curve （AUC） of RCR in predicting the 28-day all-cause mortality of AKI in ICU patients was 0.62 （95%CI：0.556-0.690，P<0.001）.ConclusionAn increase in RCR is significantly associated with an elevated 28-day all-cause mortality among patients with AKI in the ICU， and it has certain predictive value for the short–term prognosis of these patients. Clinicians should pay more attention to patients with RCR > 1.926 to enable early intervention and improve their prognosis.